Enhancing malaria elimination in high-transmission settings: the synergy of concurrent vector control and chemotherapy - Ronald Mulebeke; Adoke Yeka; Jean-Pierre van Geertruyden (Malaria Journal)
Abstract Background Malaria elimination, defined as interrupting local transmission and reducing cases to zero, is a critical public health goal. While a dual parasite-vector approach is essential, the path to elimination is complex and marked by both progress and setbacks. Despite renewed commitment and initiatives like the "High Burden High Impact" approach, challenges persist, particularly in sub-Saharan Africa. These include shifting epidemiological profiles, weak health systems, drug and insecticide resistance, and emerging global issues. Effective elimination, therefore, requires a multi-pronged approach, scaling-up a package of interventions tailored to transmission intensity, including prompt treatment with ACT, IPTp for pregnant women, vector control measures like IRS and LLINs, and robust community engagement. Ultimately, a combination of contextually appropriate strategies, implemented synergistically, will be crucial to breaking the transmission cycle and achieving sustained malaria elimination. This report aims to review the available evidence on the strategies and deployment of current tools targeting vectors and parasites in resource-limited settings, focusing on sub-Saharan Africa. Recent findings Combining malaria interventions can create a synergistic effect, where the combined impact is greater than the sum of individual interventions. For example, simulations show benefits from combining MDA and IRS, vaccines and bed nets, or the RTS,S vaccine with perennial malaria chemotherapy. However, synergistic effects are not always guaranteed; some combinations, like LLINs and IRS, may not provide additional benefit. Conversely, combining IRS and MDA, or SMC with seasonal malaria vaccination, has demonstrated increased protective effects. Therefore, successful elimination efforts depend on country-specific factors including malaria burden, political commitment, and health system capacity. However, significant biological and operational challenges remain, which may necessitate contextually appropriate approaches to achieve malaria elimination. Conclusion Synergistic intervention effects are crucial, but implementation context is paramount. While combining malaria interventions can be highly effective, not all combinations yield equal results. Thus, tailoring strategies to the specific local context and transmission dynamics is essential for maximizing impact. Moreover, successful malaria elimination is heavily reliant robust health systems and understanding the biological and operational challenges. Consequently, adaptable, evidence-based strategies are required to overcome these obstacles and achieve lasting progress toward malaria elimination.